Apocyclops cmfri sp. nov. (Cyclopoda : Cyclopoida : Cyclopidae), a new copepod species from marine waters of Karwar, Karnataka, India - Loka, Jayasree; Philipose, K. K.; Sonali, S. M.; Santhosh, B.; Anzeer, F. Muhammed; Saha, Purbali; Sukumaran, Sandhya; Kumar, Rahul G.; Gopalakrishnan, A. (Indian Journal of Fisheries, 2017)
A new species of Apocyclops Lindberg (Cyclopoda: Cyclopoida: Cyclopidae) is described based on specimens collected from marine waters of Karwar, Karnataka, India. At present, there are 11 valid and accepted species excluding one extinct species (fossil) in this genus which are widely distributed in fresh and brackishwater areas in the tropics and subtropics. Five valid species of Apocyclops are reported from the Asian region, including two species from India. The new species is closer to the previously reported Indian species, A. royi (Lindberg) and A. dengizicus dengizicus (Lepeshkin). Apocyclops cmfri sp. nov. differs from these in the size of caudal rami, in the characteristic shape of disto-medial part of coxa and basis of first to fourth pleopods (P1-P4) and in the presence of a single broad spinous expansion with a pointed tip in between exopod and endopod in basis of P1 to P4. Only one terminal spine is present in the second segment of endopod of P1. In P2 to P4, both exopod and endopod terminate in a spine and a seta of almost equal size. Maxillule highly dentate and maxilla basis form a large dentate claw with inner serration. All these characters form distinct identification features of the new species in comparison with the 12 accepted species under the genus. A key to all the species of the genus including the newly described species is proposed here. Molecular identification of the new species was carried out by mitochondrial cytochrome c oxidase 1 (CO1) gene sequencing and the sequence was submitted to NCBI, GenBank. Genetic differentiation and divergence between A. cmfri sp. nov. and species belonging to other closely related genera; Thermocyclops, Mesocyclops and Eucyclops were compared using CO1 gene sequences. The new species belonging to Apocyclops showed significant divergence from Apocyclops borneoensis with K2P value of 10.2% and from species under the genera Mesocyclops, Thermocyclops and Eucyclops with K2P values of 26.6, 27.5and 34.9% respectively.